Processing of Protein Concentrate from Some Poultry Wastes - El-Hassoon, Ahmed Shihab Hamad (Iraqi Journal of Aquaculture, 2022)
The present study aims to utilize the poultry wastes (heads & legs of chicken) in the production of protein concentrate. The chemical contents and functional properties of the final processed product were evaluated. The chemical method had been used in protein concentrate processing which included digestion of raw materials with 5 % HCl at pH 4. The chemical composition of dried poultry refusals were 46.38% protein ( N×6.25), 22.34 % fat and 8.46 % ash, while that for the processed. Protein concentrates were 77.81 % protein (N×6.25), 6.75% fat and 10.20 % ash. The obtained yield was 39.4 %. The processed product is characterized with brown color and acceptable light chicken smell, and also showed good strong stability after 90 days of storage at 28 ºC, 10 ºC and -4 ºC without objectionable changes in both color and smell. The processed product also had low total bacterial counts which were 424, 405 and 387 CFU/ gm after 90 days for the above degrees respectively, as well as c. form bacteria was not detected. The total volatile nitrogen bases (TVNB) were 8.8, 8.7 and 8.3 mg N/100 gm, while TBA values were 0.288, 0.288 and 0.283 mg melon aldehyde / kg at the same above mentioned storage temperature respectively.